Memories of the teacher (on the 120th anniversary of the birth of Academician of the USSR Academy of medical sciences D.D. Yablokov) - R. S. Karpov (Бюллетень сибирской медицины)
The article presents the analysis of the creative heritage of the outstanding physician, teacher, scientist, Academician of the USSR Academy of Medical Sciences D.D. Yablokov in connection with the 120th anniversary of his birth.